(untitled) (Itinera, 2019)
Sonia Bergamasco’s adaptation of L’Homme semence by Violette Ailhaud makes use of a single actor reciting, even if, in a staging that emphasizes plurimediality, it is not possible to define L’uomo seme as a real monologue. The analysis will take into account first the structure of the story, the strains that the plot imposes on the fabula and the effects it has on its global meaning; the linguistic marks that oppose the choral speech to the individual discourse, and the mentions referring to a culture anchored in a territory in a precise moment of history, which are superimposed on a speech that touches on the universal. Adaptation, réécriture, Ailhaud, Homme semence, théâtre